Exaustão das águas: o que mudou no Rio Toledo e no potencial hídrico no município de Toledo – PR no período de 1985 a 2010 - Pereira, Eloisa Antunes (2016)
Water is essential for the survival of living beings and in recent decades the debate on its availability and quality for future generations has increased, because the data and information in the literature about it have shown worrying results from an environmental point of view. The aim of this paper is to present a historical overview of the water quality in Toledo river and water availability in the city of Toledo - Paraná. For this purpose, documentary analysis of Toledo river water analysis reports and information from official organs were realized, as well as a literature review of the main Brazilian legislation for environmental preservation. The study shows that the municipal demand for water use has increased considerably in recent decades, and that its main source has been suffering the effects of the occupation of their surroundings and the discharge of effluents. The index of water quality in Toledo river demonstrated values ranging for smaller and smaller indexes along its route, indicating degradation of their ecosystem. The guarantee of water resources for future use depends on more attention from the managers and the public in relation to its use.